A Decision-Making Framework for University Student Sports Study Psychological Healthy Evaluation with 2-Tuple Linguistic Neutrosophic Numbers - Xiaoping Yang; Wensheng Shi (Discrete Dynamics in Nature and Society)
A healthy body is the foundation of education, and the guiding ideology of health first requires that all educational work in schools should take the health of students as the starting point and be responsible for the health of students. Taking the development of students as the foundation, its essential meaning is to make students develop into a “complete person,” that is, to integrate and unify students’ morality, intelligence, physique, beauty, life, habits, morality, skills, and other elements. The establishment of the evaluation index system of sports health literacy is a complex evaluation system with multiple factors and multiple indicators. The university student sports study psychological healthy evaluation is always looked as the multiple attribute decision-making (MADM) issue. In this paper, based on the generalized Heronian mean (HM) operator and generalized weighted HM (GWHM) operator, the generalized 2-tuple linguistic neutrosophic HM (G2TLNHM) operator and generalized 2-tuple linguistic neutrosophic weighted HM (G2TLNWHM) operator are proposed with 2-tuple linguistic neutrosophic sets (2TLNSs). Finally, an example of university student sports study psychological healthy evaluation is used to show the proposed methods. Some comparative studies and parameter influence analysis on the final result are fully given. The results show that the built algorithms method is really useful for university student sports study psychological healthy evaluation.